1998
DOI: 10.1103/physrevlett.81.3112
|View full text |Cite
|
Sign up to set email alerts
|

Half-Cycle Pulse Assisted Electron-Ion Recombination

Abstract: Unipolar "half-cycle" electric field pulses (HCPs) have been used to recombine free electrons and calcium ions. The field assisted process is very similar to controlled three-body recombination in plasmas. We report on experiments that utilize HCP assisted recombination to probe the probability distribution of continuum electron wave packets and produce bound wave packets that are highly localized in three spatial dimensions.The combination of free electrons and ions to form neutral atoms is a complicated proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 18 publications
(24 reference statements)
0
22
0
2
Order By: Relevance
“…However, as with other nonresonant multiphoton phenomena, the germane physics is most easily understood in terms of momentum transfer between a classical field and a continuum electron. In fact, the process is analogous to electron-ion recombination stimulated by isolated half-cycle pulses [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, as with other nonresonant multiphoton phenomena, the germane physics is most easily understood in terms of momentum transfer between a classical field and a continuum electron. In fact, the process is analogous to electron-ion recombination stimulated by isolated half-cycle pulses [18].…”
mentioning
confidence: 99%
“…However, as with other nonresonant multiphoton phenomena, the germane physics is most easily understood in terms of momentum transfer between a classical field and a continuum electron. In fact, the process is analogous to electron-ion recombination stimulated by isolated half-cycle pulses [18].We excite electrons with well-defined energies jE 0 j < 15 cm À1 relative to the ionization threshold, in the presence of a pulsed 38.8 GHz microwave field. A novel scheme, based on radiative stabilization of autoionizing Rydberg states, facilitates pulsed field-ionization detection of only those atoms with electrons bound by <1 cm À1 following the microwave pulse [19,20].…”
mentioning
confidence: 99%
“…Meerson and Friedland [8] suggested that using a laser pulse, initially at the Kepler frequency that is chirped to lower frequency later, would transfer atoms to a higher n state, leading to ionization at a lower microwave field. Recent work of Bensky et al [9] and Wesdorp et al [10] suggested that it might be more interesting to chirp the frequency in other direction. They have demonstrated that it is possible to induce electron-ion recombination into high-lying Rydberg states with half cycle pulses, and the technique could be a way to produce antihydrogen [11].…”
Section: Introductionmentioning
confidence: 98%
“…In particular, this property can be an advantage if one wants to control the ultrafast charge motion in the pump-probe experiments. Specifically, unipolar pulses can efficiently deliver a kinetic momentum to the charged particles in order to control their motion, for instance, to ionize the atoms or ions in the medium [5][6][7] or to measure the quantum dynamics of electron and ionic wavepackets [8][9][10][11]. Unipolar pulses can efficiently accelerate the charge particles and thus be used for producing coherent beams for particle injectors and charge-particle accelerating devices [12,13].…”
Section: Introductionmentioning
confidence: 99%